Generation of OAM Radio Waves Using Circular Vivaldi Antenna Array - Changjiang Deng; Wenhua Chen; Zhijun Zhang; Yue Li; Zhenghe Feng (International Journal of Antennas and Propagation)
This paper gives a feasible and simple solution of generating OAM-carrying radio beams. Eight Vivaldi antenna elements connect sequentially and fold into a hollow cylinder. The circular Vivaldi antenna array is fed with unit amplitude but with a successive phase difference from element to element. By changing the phase difference at the steps of 0, ±45°, ±90°, ±135°, and 180°, the OAM radio beam can be generated with mode numbers 0, ±1, ±2, ±3, and 4. Simulations show that the OAM states of ±2 and ±3 are the same as the traditional states, while the OAM states of 0, ±1, and 4 differ at the boresight. This phenomenon can be explained by the radiation pattern difference between Vivaldi antenna and tripole antenna. A solution of distinguishing OAM states is also proposed. The mode number of OAM can be distinguished with only 2 receivers.